In vitro investigations on the effects of graphene and graphene oxide on polycaprolactone bone tissue engineering scaffolds - Hou, Yanhao (2024)
Polycaprolactone (PCL) scaffolds that are produced through additive manufacturing are one of the most researched bone tissue engineering structures in the field. Due to the intrinsic limitations of PCL, carbon nanomaterials are often investigated to reinforce the PCL scaffolds. Despite several studies that have been conducted on carbon nanomaterials, such as graphene (G) and graphene oxide (GO), certain challenges remain in terms of the precise design of the biological and nonbiological properties of the scaffolds. This paper addresses this limitation by investigating both the nonbiological (element composition, surface, degradation, and thermal and mechanical properties) and biological characteristics of carbon nanomaterial-reinforced PCL scaffolds for bone tissue engineering applications. Results showed that the incorporation of G and GO increased surface properties (reduced modulus and wettability), material crystallinity, crystallization temperature, and degradation rate. However, the variations in compressive modulus, strength, surface hardness, and cell metabolic activity strongly depended on the type of reinforcement. Finally, a series of phenomenological models were developed based on experimental results to describe the variations of scaffold’s weight, fiber diameter, porosity, and mechanical properties as functions of degradation time and carbon nanomaterial concentrations. The results presented in this paper enable the design of three-dimensional (3D) bone scaffolds with tuned properties by adjusting the type and concentration of different functional fillers. Graphic abstract: (Figure presented.)